Radio-opaque agents in bone cement increase bone resorption. - Sabokbar, A; Fujikawa, Y; Murray, D; Athanasou, N (1997)
A heavy infiltrate of foreign-body macrophages is commonly seen in the fibrous membrane which surrounds an aseptically loose cemented implant. This is in response to particles of polymethylmethacrylate (PMMA) bone cement and other biomaterials. We have previously shown that monocytes and macrophages responding to particles of bone cement are capable of differentiating into osteoclastic cells which resorb bone. To determine whether the radio-opaque additives barium sulphate (BaSO4) and zirconium dioxide (ZrO2) influence this process, particles of PMMA with and without these agents were added to mouse monocytes and cocultured with osteoblast-like cells on bone slices. Osteoclast differentiation, as shown by the presence of the osteoclast-associated enzyme tartrate-resistant acid phosphatase (TRAP) and lacunar bone resorption, was observed in all cocultures. The addition of PMMA alone to these cocultures caused no increase in TRAP expression or bone resorption relative to control cocultures. Adding PMMA particles containing BaSO4 or ZrO2, however, caused an increase in TRAP expression and a highly significant increase in bone resorption. Particles containing BaSO4 were associated with 50% more bone resorption than those containing ZrO2. Our results suggest that radio-opaque agents in bone cement may contribute to the bone resorption of aseptic loosening by enhancing macrophage-osteoclast differentiation, and that PMMA containing BaSO4 is likely to be associated with more osteolysis than that containing ZrO2.